2018
DOI: 10.1128/aac.01279-17
|View full text |Cite
|
Sign up to set email alerts
|

Mutations within embCAB Are Associated with Variable Level of Ethambutol Resistance in Mycobacterium tuberculosis Isolates from China

Abstract: The EmbCAB proteins have been considered a target for ethambutol (EMB). Mutations in are known to confer most EMB resistance. However, the knowledge about the effects of mutations on the EMB resistance level and about the role of mutation-mutation interactions is limited in China. Here, we sequenced among 125 isolates from China and quantified their EMB MICs by testing growth at 10 concentrations. Furthermore, a multivariate regression model was established to assess the effects of both individual mutations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 27 publications
1
33
1
Order By: Relevance
“…Khosravi et al reported embA mutation from EMB-susceptible strains [47]. Additionally, Sun et al revealed that 82.6% of EMB-resistant isolates from China had at least a mutation in the embABC locus, but contrary to this study, they were located mostly in the embA and embB upstream region [48].…”
Section: Discussioncontrasting
confidence: 72%
“…Khosravi et al reported embA mutation from EMB-susceptible strains [47]. Additionally, Sun et al revealed that 82.6% of EMB-resistant isolates from China had at least a mutation in the embABC locus, but contrary to this study, they were located mostly in the embA and embB upstream region [48].…”
Section: Discussioncontrasting
confidence: 72%
“…3F and 3G). We thus suggest that ethambutol preferentially binds to EmbB and EmbC rather than to EmbA, a conclusion in line with clinical drug resistance studies (3)(4)(5)(36)(37)(38)(39)(40). When superimposing the EmbB (or EmbC) subunits in complex with ethambutol and disaccharide, we found that they overlapped within a high degree of similarity ( (Fig.…”
Section: Structural Basis For Ethambutol Inhibition On Embb and Embcsupporting
confidence: 82%
“…EmbC, which are involved in cell wall biosynthesis are regarded as the targets of ethambutol, since mutations to these proteins result in TB strains that are clinically resistant to this drug, noting that the majority of these resistance sites occur within EmbB (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…This low detection rate could be attributed to a lack of appropriate probes. EMB resistance occurs most frequently at codons 306, 406, and 497 in the embB gene [26,27]; however, we designed probes related only to codon 306. Second, this study was conducted using only selected strains, including a high proportion of drug-resistant strains, and the performance evaluation was mainly focused on the detection of resistance.…”
Section: Discussionmentioning
confidence: 99%